2008
DOI: 10.1111/j.1753-6405.2008.00185.x
|View full text |Cite|
|
Sign up to set email alerts
|

The social determinants of being an Indigenous non‐smoker

Abstract: Objective: To examine the association between various social factors and being a non‐smoker in a national survey of Aboriginal and Torres Strait Islander people aged 15 and over. Methods: We analysed data from the 2002 National Aboriginal and Torres Strait Islander Social Survey (n=9,400) using logistic regression. Results: About a half (51.2%) of the Aboriginal and Torres Strait Islander population aged 15 years and over smoked, 33.4% had never smoked, and 15.4% were ex‐smokers. Higher socio‐economic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 7 publications
3
77
0
Order By: Relevance
“…A study of the social determinants of Indigenous nonsmoking (Thomas et al 2008) found that while there are some variations with age, gender and geographic location, the most significant determinant of Indigenous nonsmoking behaviour was socio-economic position. In this study, Indigenous people who had been arrested in the last five years, removed from their natural family or had not abstained from alcohol were also more like to be smokers than those who were not, yet these factors were not as significant in influencing smoking cessation.…”
Section: Scrutinising the Social In Indigenous Smoking Cessationmentioning
confidence: 98%
“…A study of the social determinants of Indigenous nonsmoking (Thomas et al 2008) found that while there are some variations with age, gender and geographic location, the most significant determinant of Indigenous nonsmoking behaviour was socio-economic position. In this study, Indigenous people who had been arrested in the last five years, removed from their natural family or had not abstained from alcohol were also more like to be smokers than those who were not, yet these factors were not as significant in influencing smoking cessation.…”
Section: Scrutinising the Social In Indigenous Smoking Cessationmentioning
confidence: 98%
“…In contrast to alcohol, tobacco use in the Indigenous community has received significantly less attention in the media and, until recently, in government policy and program funding. This is despite 50% of Indigenous adults being daily smokers and smoking being the leading cause of death and disability for Indigenous Australians [4,5].…”
Section: A T the National Indigenous Health Equality Summit Inmentioning
confidence: 97%
“…In contrast, just 19.2% of Victorian adults were regular smokers in 2002 [4]. While Aboriginal women are more likely than Aboriginal men to be non-smokers and to have never smoked [3], Aboriginal women are 2.5 times more likely to smoke than non-Aboriginal women [5].…”
Section: Introductionmentioning
confidence: 98%
“…As noted in the National Aboriginal and Torres Strait Islander Health Survey, 2004-2005, Aboriginal people are more than twice as likely to smoke than non-Aboriginal people in Australia [2]. Gender-and age-adjusted data from the 2002 National Aboriginal and Torres Strait Islander Social Survey indicates that 53.5% of Aboriginal Victorians aged over 15 are current smokers [3]. In contrast, just 19.2% of Victorian adults were regular smokers in 2002 [4].…”
Section: Introductionmentioning
confidence: 99%